Contribution to the study of deep coastal detritic bottoms: the algal communities of the continental shelf off the Balearic Islands, Western Mediterranean - JOHER, S.; BALLESTEROS, E.; RODRIGUES-PRIETO, C. (Mediterranean Marine Science, 2015)
Three main algal-dominated coastal detritic communities from the continental shelf off Mallorca and Menorca (Balearic Islands, Western Mediterranean) are described herein: maërl beds dominated by Spongites fruticulosus and forests of Laminaria rodriguezii located in the Menorca channel, and Peyssonnelia inamoena beds found along the Southern coast of Menorca. There seems to be a gradient of disturbance from the highly disturbed Peyssonnelia beds to the almost undisturbed L. rodriguezii forests. Whether this gradient is the result of current and past anthropogenic pressure (e.g. trawling intensity) or is driven by natural environmental factors needs further assessment. Finally, the location of the target communities by means of ROV dives combined with the use of a Box-Corer dredge and beam trawl proved to be a good methodology in the study of the composition and structure of these deep water detritic communities.